2009
DOI: 10.1109/ted.2009.2015854
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Optimization of Hot-Carrier Reliability in Germanium-on-Silicon pMOSFETs

Abstract: Abstract-In this paper, a comprehensive study of hotcarrier injection (HCI) has been performed on high-performance Si-passivated pMOSFETs with high-k metal gate fabricated on n-type germanium-on-silicon (Ge-on-Si) substrates. Negative bias temperature instability (NBTI) has also been explored on the same devices. The following are found: 1) Impact ionization rate in Ge-on-Si MOSFETs is approximately two orders higher as compared to their Si counterpart; 2) NBTI degradation is a lesser concern than HCI for Ge-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 16 publications
(25 reference statements)
0
5
0
1
Order By: Relevance
“…Good obtained for Si-capped Ge MOSFETs [4], and their NBTI was found to be better than Si counterparts [2], [5]. Electron trapping, however, needs investigation.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Good obtained for Si-capped Ge MOSFETs [4], and their NBTI was found to be better than Si counterparts [2], [5]. Electron trapping, however, needs investigation.…”
Section: Introductionmentioning
confidence: 95%
“…The reported Ge MOSFETs capped by a few Si monolayers generally have much shorter channel length and thinner dielectrics than those without them [1]- [3]. The process for fabricating Si-capped Ge MOSFETs is becoming sufficiently mature to warrant research into their reliability, and some encouraging results have been reported [4], [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IMEC做了Ge pMOSFET的TDDB特性研究, 发 现和Si器件差别不大 [51] . IMEC和印度理工学院对Ge pMOSFET的HCI做了初步研究, 由于Ge带隙较窄, Ge pMOSFET中碰撞电离效应几乎是Si器件的两倍, 导致 HCI效应恶化 [52] . 加州大学伯克利分校的Hu教授 [3] 提出绿色晶体 管的概念, 他指出TFET可以在超低工作电压下实现比 MOSFET更低的能耗.…”
Section: Gesn沟道nmosfetunclassified
“…Several studies [16][17][18][19][20] the BTI reliability in Ge MOSFETs. The devices with HfO 2 /SiO 2 gate stack show less than the Si counterparts [16][17][18][19] because t trapping in the dielectric of the Ge device due t band offset. The PBTI degradation of the G severe than the Si counterparts [16].…”
Section: Introductionmentioning
confidence: 99%